Characterization of polyamidoamino (PAMAM) dendrimers using in-line reversed phase LC electrospray ionization mass spectrometry. Issue 2 (16th December 2015) - Lloyd, John R.; Jayasekara, P. Suresh; Jacobson, Kenneth A.
Abstract : Generation 3 (G3) PAMAM dendrimers are symmetrical, highly branched polymers widely reported in the scientific literature as therapeutic agents themselves or as carrier scaffolds for various therapeutic agents. Abstract : Generation 3 (G3) PAMAM dendrimers are symmetrical, highly branched polymers widely reported in the scientific literature as therapeutic agents themselves or as carrier scaffolds for various therapeutic agents. A large number of analytical techniques have been applied to study PAMAM dendrimers, but one that has been missing is in-line reversed phase LC electrospray ionization mass spectrometry (RP/LC/ESI/MS). To translate PAMAM dendrimers into therapeutic agents, a better understanding of their purity, stability and structure is required, and in-line RP/LC/ESI/MS is widely applied to all three of these analytical questions. In this study, we developed a robust in-line RP/LC/ESI/MS method for assessing stability, purity and structure of the G3 PAMAM dendrimers, and we also examined the reasons why previous attempts at method development failed. Using the RP/LC/ESI/MS method we uncovered several unique aspects of the chemistry of G3 PAMAM dendrimers. They are interconverted between two isomeric forms by dialysis, and under higher concentration levels there is an inter-molecular displacement reaction resulting, which degrades PAMAM dendrimers. Purification of G3 dendrimers by RP/LC was also previously unreported; so we slightly modified the LC/MS method for isolating individual components from a complex dendrimer mixture. Thus, we have developed a robust, comprehensive method for characterizing PAMAM dendrimers and their degradation.